PROTOTYPING A SYSTEM OF AN EARLY BUILDING DAMAGE ASSESSMENT EFFECTED BY AN EARTHQUAKE - Wahyu Ramadhan; Jamaludin Jamaludin (Universitas Teknologi Mataram, 2021)
The main purpose of this research is to identify a level of a building damage caused by an earthquake early and in detail by utilizing an information system. Early identification of the building damage will be categorized based on three categories, namely minor damage, moderate damage and major damage. Each classification has standards and calculations set up by the government. To find out the damage categories, a current study was carried out on how to develop an information system that could be used by evaluators in determining conclusions according to observation results. Related to the research and development method, and adapting the Analysis, Design, Development, Implementation and Evaluation (ADDIE) development model, researchers collaborate between the ADDIE model and the standard building damage values decided by the government in a real time. The design of the early damage assessment tool for buildings is still under development and is still a prototype system.